Green information technology system practice for sustainable collaborative enterprise: A structural literature review - Anthony Jr, Bokolo; Mazlina, Abdul Majid; Awanis, Romli (Inderscience Enterprises Ltd., 2017)
Green information technology and information system (ITIS) refer to sustainable practices that seek to prevent environmental pollution and attain sustainable development in collaborative enterprise (CE). By implementing green ITIS practices, collaborative enterprise can reduce the amount of energy used; decrease high cost incurred in their business process and also care for the long time sustainability of the environment and humanity. Therefore, the purpose of this research paper is to a carryout a structural literature review approach to review existing techniques applied to achieve sustainability and standards deployed to assist practitioners in implementing and diffusing green practices in CE. Finding from this review indicates that previously applied techniques and standards lacks the capability to support IT practitioners in making green decisions on how to implement and adopt sustainable practice in collaborative enterprise.